PENINGKATAN KUALITAS JASA DAN PRODUKTIVITAS HASIL PENELITIAN BALAI ARKEOLOGI YOGYAKARTA - Indah Asikin Nurani (Balai Arkeologi Yogyakarta, 2010)
As research institute, the performance of Balai Arkeologi Yogyakarta is determined by the guality and productivity in disseminating and publishing the results of their research to the public. In the era of digitization, it is necessary for the institute to enhance their service to the public, especially academia as well as other stakeholders. To attain this, Balai Arkeologi Yogyakarta, through its Documentation and Information Working Group, attempts to improve its performance in the management of data by converting the research data from hard copy into soft copy. Such improvement is solely intended to enhance the service guality and productivity of the institution to the public. The important role of the institution will not be appreciated by public if the institution is unable to deliver the results of their research in good and attractive presentation. Therefore, service marketing approach needs to be applied to improve the dissemination of service and information by Balai Arkeologi Yogyakarta. This article describes how the improvement of service guality and productivity of research results are carried out in the institution.